Implementasi Smart Governance Melalui Layanan Digital Berbasis Web di Desa Jamali Kabupaten Cianjur Jawa Barat - Darmadi, Roby; Nugraha, Mara; Fadlilah, Fikri; Suryadithia, Rachmat; Al Kautsar, Hanggoro Aji (Jurnal Pengabdian UNDIKMA, 2025)
This community service aims to implement the concept of smart villages through the application of web-based information systems to support smart governance of village governments that are more efficient and transparent. The method used in this community service activity is training and mentoring with the stages of planning, design, development, expert judgment, and system implementation which includes digital information services, making certificates, community complaints, and managing population data. The evaluation instrument for this activity uses a questionnaire with quantitative descriptive data analysis techniques.Â  The results of this service activity show that the web-based information system developed has succeeded in increasing efficiency in the village administration process, accelerating access to information for the community, and increasing transparency in public services. The training provided was able to improve the understanding and ability of village officials in using the system. The implementation of a digital information system in Jamali Village is expected to encourage the creation of a more responsive and efficient village government, providing a positive impact on improving the quality of public services in the future.